Signification of Depth of Penetration in Eddy Current Non-Destructive Testing - Tomas Marek (Communications - Scientific letters of the University of Zilina, 2005)
Eddy currents are utilized for non-destructive testing of conductive materials. The depth of penetration is a very important parameter as it defines the propagation of the electromagnetic wave as well as of the electromagnetic energy in conductive materials. Limitations of the nondestructive testing using eddy currents are therefore given by the parameter. The paper highlights the signification of the depth of penetration in eddy current non-destructive testing using numerical simulations. A tubular specimen with a defect of a variable depth is inspected using a bobbin type probe and the crack signals are calculated for the purpose. The finite element method is used for the numerical study.